2022
DOI: 10.1007/s10546-022-00700-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Measurement Height and Low-Pass-Filtering Corrections on Eddy-Covariance Flux Measurements Over a Forest Clearing with Complex Vegetation

Abstract: Flux measurements over heterogeneous surfaces with growing vegetation and a limited fetch are a difficult task, as measurement heights that are too high or too low above the canopy adversely affect results. The aim of this study is to assess implications from measurement height in regard to low-pass filtering, footprint representativeness, and energy balance closure for a clear-cut site with regrowing vegetation of varying height. For this, measurements from two open-path eddy-covariance systems at different h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…The results showed that the relative effect of the spectral correction method on the flux magnitude increases with higher spectral correction factors, or in other words, with an increasing loss of high-frequency signal. When the relative importance of the spectral correction method increases, systematic small differences between spectral correction methods are added up and the difference between spectral methods and the total uncertainty of the flux increases (Mauder and Foken, 2006;Reitz et al, 2022). As the LC-EC per definition has stronger loss of high-frequency signal, applying the right spectral correction method is more important compared to CON-EC.…”
Section: Effect Of the Spectral Correction Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that the relative effect of the spectral correction method on the flux magnitude increases with higher spectral correction factors, or in other words, with an increasing loss of high-frequency signal. When the relative importance of the spectral correction method increases, systematic small differences between spectral correction methods are added up and the difference between spectral methods and the total uncertainty of the flux increases (Mauder and Foken, 2006;Reitz et al, 2022). As the LC-EC per definition has stronger loss of high-frequency signal, applying the right spectral correction method is more important compared to CON-EC.…”
Section: Effect Of the Spectral Correction Methodsmentioning
confidence: 99%
“…Based on our results, and especially the better energy balance closure and energy balance ratio, the Horst (1997) method was chosen as preferred spectral correction method in the current study, even though the Ibrom et al (2007) method was designed for closed path EC setups. As the LC-EC fluxes where still deviating from the CON-EC, it would be interesting to test a wide variety of other spectral correction methods in the future, especially because the system design of the LC-EC is different from CON-EC setups which have been used and thoroughly tested in the past (Polonik et al, 2019;Reitz et al, 2022).…”
Section: Effect Of the Spectral Correction Methodsmentioning
confidence: 99%
See 3 more Smart Citations